Molecular Detection of Marine-Borne Pathogen Vibrio cholerae in Traditional Fermented Shrimp Paste from East Lombok using Polymerase Chain Reaction - Firman Perdhana; Muhammad ‘Aidil Febriandito; Mutia Devi Ariyana; Lalu Unsunnidhal; Ines Marisya Dwi Anggraini; Baiq Rien Handayani; Lulu Diani Zuhdia (Westscience Press, 2026)
Terasi is a traditional Indonesian fermented shrimp paste produced by local MSMEs, often under handmade conditions that raise concerns regarding the presence of marine-borne pathogens. This study aimed to perform molecular surveillance of Vibrio cholerae in matured solid block terasi from three prominent MSMEs in East Lombok using Polymerase Chain Reaction (PCR). Six samples from different production batches were evaluated. The methodology integrated physicochemical analysis ( and pH), and PCR detection targeting the F0316_RS13020 gene. Results showed that all samples possessed a low ranging from 0.63 to 0.66 and alkaline pH levels between 7.72 and 8.07. Molecular detection yielded negative results for V. cholerae across all samples, while the positive control was successfully amplified at the 637 bp target size. The absence of this pathogen is attributed to the synergistic hurdle technology of high salinity, low , and high-temperature roasting (up to 260°C), which inhibits Vibrio survival. This study confirms that matured terasi from East Lombok meets the microbiological safety criteria. Future monitoring should focus on raw materials using viability-based PCR to further enhance regional food safety surveillance, especially from fish and fishery products.